Compression Ignition Engines – Revolutionary Technology That has Civilized Frontiers all Over the Globe from the Industrial Revolution into the Twenty-First Century - Ciatti, Stephen A. (Frontiers in Mechanical Engineering, 2015)
The history, present and future of the compression ignition engine is a fascinating story that spans over 100 years, from the time of Rudolf Diesel to the highly regulated and computerized engines of the 21st Century. The development of these engines provided inexpensive, reliable and high power density machines to allow transportation, construction and farming to be more productive with less human effort than in any previous period of human history. The concept that fuels could be consumed efficiently and effectively with only the ignition of pressurized and heated air was a significant departure from the previous coal-burning architecture of the 1800s. Today, the compression ignition engine is undergoing yet another revolution. The equipment that provides transport, builds roads and infrastructure, and harvests the food we eat needs to meet more stringent requirements than ever before. How successfully 21st Century engineers are able to make compression ignition engine technology meet these demands will be of major influence in assisting developing nations (with over 50% of the world’s population) achieve the economic and environmental goals they seek.